HUBUNGAN RELATIVE FAT MASS DENGAN UKURAN DAN JUMLAH BATU EMPEDU PADA PASIEN PEREMPUAN KOLESISTOLITIASIS - Yuliza Birman; Ahmad Fajar Bahri; Rosmaini Rosmaini; Ade Teti Vani; Mhd Nurhuda; Muhamad Ivan (Yayasan Nusantara Hasana Berdikari, 2026)
Background: Cholelithiasis is frequently associated with obesity. Relative Fat Mass (RFM) is considered a more representative indicator of adiposity than body mass index because it reflects body fat distribution. However, studies examining the association between Relative Fat Mass and gallstone characteristics remain limited. Objective: To determine the association between Relative Fat Mass (RFM) and gallstone size and number among female patients with cholelithiasis. Methods: This observational analytic study employed a cross-sectional design involving 64 female patients with cholelithiasis at RSI Siti Rahmah Padang in 2025. Relative Fat Mass was categorized as ≤37% and >37%. Gallstone size was classified as ≤10 mm and >10 mm, while the number of gallstones was categorized as single or multiple. The associations were analyzed using the ordinal Gamma correlation test. Results: Most participants had Relative Fat Mass >37% (57.8%), gallstone size >10 mm (59.4%), and multiple gallstones (65.6%). A significant association was found between Relative Fat Mass and gallstone size (p = 0.007; r = 0.594). However, no significant association was observed between Relative Fat Mass and the number of gallstones (p = 0.703; r = 0.101). Conclusion: Relative Fat Mass is significantly associated with gallstone size but not with the number of gallstones among female patients with cholelithiasis.